2014
DOI: 10.5897/ijeaps2014.0342
|View full text |Cite
|
Sign up to set email alerts
|

Institutional factors as predictors of students academic achievement in colleges of education in South western Nigeria

Abstract: The enhancement of the academic achievement of the Nigerian students has continued to engage the attention of educational practitioners and policy makers. This paper investigated institutional factors as predictors of students' academic performance in Colleges of Education in South-Western Nigeria. The study employed the ex post facto design using a survey design and a multiple regression model. The samples used for the study consisted of 1,100 (200 and 300 levels) National Certificate of Education (NCE) stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 9 publications
3
16
0
Order By: Relevance
“…Applied here were: resources as the independent variable, engagement as the mediating variable, and student learning outcomes as the dependent variable. Although many studies have shown a statistically relevant and positive correlation between demographic factors such as residence status (Astin, 1999;Pascarella, Bohr, Nora, Zusman, Inman, & Desler, 1994), gender, and teacher qualification (Adeyemi & Adeyemi, 2014;Nurhadi, Zahro, & Lyau, 2017) on the one hand, and academic achievement on the other, the present study found out that gender, residence status, faculty qualification, and students' area of specialization did not lead to significant differences between the groups, and therefore, these factors were not considered determinant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applied here were: resources as the independent variable, engagement as the mediating variable, and student learning outcomes as the dependent variable. Although many studies have shown a statistically relevant and positive correlation between demographic factors such as residence status (Astin, 1999;Pascarella, Bohr, Nora, Zusman, Inman, & Desler, 1994), gender, and teacher qualification (Adeyemi & Adeyemi, 2014;Nurhadi, Zahro, & Lyau, 2017) on the one hand, and academic achievement on the other, the present study found out that gender, residence status, faculty qualification, and students' area of specialization did not lead to significant differences between the groups, and therefore, these factors were not considered determinant.…”
Section: Discussionmentioning
confidence: 99%
“…This is because learning involves interaction between students and their environment. The availability of adequate physical resources was found to have a significant contribution on students' academic achievement (Adeyemi & Adeyemi, 2014).…”
Section: Physical Resourcesmentioning
confidence: 98%
“…A failure to appropriately supervise instruction on the part of teachers might result in the failure of supervisory programme, which is a critical factor for school administration. The person who is task with the responsibility of supervision is the school head (Adeyemi, 2010). Despite the fact that supervision is very important in evaluating the effectiveness of schools, it is disturbing to note that it is irregularly conducted (Ezekwesili, 2007 and scarce number of qualified school supervisors.…”
Section: Supervisionmentioning
confidence: 99%
“…School teachers should be made to understand that they can reach out to the school head with their grievances and obtain backing. In fact, Adeyemi (2010) opines that the way a school head relates with his or her staff has a positive or negative impact on the productivity level of the staff. In the same vein, the school head is in a solely in-charge as the administrator, who control school's resources for the purpose of attaining the aims and objectives of his school (Ikegbusi, 2014).…”
Section: School Head-teacher-community Relationshipmentioning
confidence: 99%
“…In most of the Nigerian institutions, it was observed that lack of concentration, lack of teaching equipment, lack of manpower, poor understanding of concept, inability to study well, poor attitude towards learning, and pleasure seeking attitude contribute to low academic performance. 4 Most of the negative consequences in the behaviour of students arise as a result of alcohol abuse. 5 Alcohol abuse among the university students has been studied for many decades starting with the work of Straus and Bacon.…”
Section: Introductionmentioning
confidence: 99%